1996
DOI: 10.1002/hlca.19960790519
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2′‐Deoxy‐5‐(isothiazol‐5‐yl)uridine and Its Interaction with the HSV‐1 Thymidine Kinase

Abstract: (1 3.11.96) 2'-Deoxy-5-(isothiazol-5-yl)uridine (12) was synthesized starting from 2'-deoxy-5-iodouridine using a Pdcatalysed cross-coupling reaction with propiolaldehyde diethyl acetal followed by deprotection and ring closure using thiosulfate. 2'-Deoxyuridine 12 has a particular place among the 5-heteroaryl-substituted 2'-deoxyuridines in that it has a high affinity for herpes simplex virus type 1(HSV-1)-encoded thymidine kinase (TK) without antiviral activity. Biochemical studies revealed that 12 is a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(7 reference statements)
3
4
0
Order By: Relevance
“…Interestingly, in the 2-thienyl series of compounds, coplanarity is stabilized by an interaction between the O4 carbonyl group of the uracil base and the sulfur atom of the thiophene ring (Figure , structure A ). A similar orientation for the isothiazole derivative (Figure , structure B ) has been deduced from its NMR spectrum and quantum-chemical calculations, which predict a stability of 17 kJ/mol of the NMR observed orientation relative to the other possibility , structures C and D ).…”
Section: The Playerssupporting
confidence: 67%
“…Interestingly, in the 2-thienyl series of compounds, coplanarity is stabilized by an interaction between the O4 carbonyl group of the uracil base and the sulfur atom of the thiophene ring (Figure , structure A ). A similar orientation for the isothiazole derivative (Figure , structure B ) has been deduced from its NMR spectrum and quantum-chemical calculations, which predict a stability of 17 kJ/mol of the NMR observed orientation relative to the other possibility , structures C and D ).…”
Section: The Playerssupporting
confidence: 67%
“…19 The structural results presented here imply that this could be due to the size of the bromovinyl moiety, by comparison with the iodine of IDU or AHIU or the bromothienyl group of BTDU, being such as to give an optimal fit to this site (allowing for the observed movement of Tyr-132), in terms of van der Waals interactions. The compound 5-thienyluridine, not yet examined by us, shows a strength of binding 18,19 similar to BTDU; it is possible the five-membered ring of this and BTDU is slightly too bulky for the subsite. Figure 5b shows an overlay of the active site regions of the TK/ ganciclovir and TK/BVDU complexes, and emphasizes the considerable, albeit flat, volume which is available for ligand binding in the enzyme.…”
Section: Subsites Of Ligand Bindingmentioning
confidence: 96%
“…It is observed that the 2-amino group, carbonyl groups and the nitrogen atom of the benzoisoquinoline-1,3-dione moiety form five H-bond interactions with Glu63 and Tyr172, with bond lengths of 2.53, 3.27, 3.01, 3.38 and 3.31 Å, respectively. In addition, the hydrophobic interactions with Tyr172 alongside the phenyl ring with Tyr132 and Trp88 appear to constrain the molecule in close proximity with the amino acids forming the aforementioned hydrogen bonding [24,25,26].…”
Section: Resultsmentioning
confidence: 99%